The influence of behavioural and socioeconomic factors on the community injury rates of adolescents assessed by the south Korean emergency medical services: an ecological approach - Ki Ok Ahn; Jungeun Kim; Sang Do Shin; Hyesook Park; Federico E. Vaca; Ju Ok Park (BMC, 2019)
Abstract Background Aim of this study is to determine if peer group risk behaviors and neighbourhood socioeconomic status (SES) would ecologically affect injury incidence according to place and gender among adolescents (aged 13-15) in South Korea. Methods Three variables from the Korea Youth Risk Behavior Survey (2014) were used to represent peer group risk behaviours; current alcohol consumption (cAlc), the experience of violence or bullying (VicVB), and having undergone education for injury prevention (Edu-IP). The Korea Census Data (2010) was used for neighborhood SES; the degree of urbanization, the proportion of high educational attainment, and the proportion of low residential environment. The nationwide and regional Incidence-Rates of Injury assessed by EMS (IRI-EMS) were calculated according to age and gender based on the number of injuries from EMS record (2014). A linear regression model was used to examine associations. Results The nationwide total and inside-school IRI-EMS were 623.8 and 139.3 per 100,000 population, respectively. The range of the regional IRI-EMS showed a maximum of about 4 times the difference from 345 to 1281 per 100,000 population depending on the region. The low residential environment had a significant effect on the increase of total IRI-EMS (β = 7.5, 95% CI 0.78-14.21). In the case of boys, the IRI-EMS inside-school was increased as the percentage of VicVB was higher (β = 17.0, 95% CI 1.09-32.91). In the case of girls, the IRI-EMS outside-school was increased in rural compared to urban location (β = 211.3, 95% CI 19.12-403.57). Conclusion The incidence rate of outside-school was higher than that of inside-school, and incidence rate of boys was higher than that of girls. Peer group risk behaviors were significant only in the injury of boys. Among the SES factors, rural area was a significant factor in girls, especially outside-school injury. Moreover, the rate of households not in an apartment was significant in all outside-school injury and outside-school injury of boys. Our study suggests that among native South Korean adolescents, neighbourhood SES and peer group risk behavior have different effects depending on the injury context such as place of occurrence or gender.